MEMBANGKITKAN RASA INGIN TAHU ANAK USIA DINI DENGAN CINTA DAN CERDIK - Endang Lestari; Rifa Suci Wulandari (QURROTI, 2021)
The purpose of this study was to see how to arouse children's curiosity with love and cleverness. This research was conducted at Mardisiwi Kindergarten, Kedondong Village, Kebonsari District, Madiun Regency, East Java. The type of research used is descriptive qualitative. Data collection by observation and interviews, data analysis and research results in the form of a description. Educating with love is to prove love to children and have a good attitude. While educating smartly is by understanding the child's character, PAUD children develop characteristics, appearance, fluctuating, images, gifts, ideas or ideas, creative, flexible, fun at all times, for me to you, and the times. From the results of the study that educating with love and showing can arouse the curiosity of children in Mardisiwi Kindergarten, Kedondong Village, Kebonsari District, Madiun Regency, East Java.